Perseverance [large type] - Dearen, Patrick (Wheeler Publishing large print softcover western, 2023)
It was 1932, the depths of the Great Depression, and thousands of desperate people rode the rails in search of jobs, homes, and hope. For some, the tracks were a road to nowhere, a dead end in a boxcar or under the wheels or in a sea of emptiness. Their fate seemed certain-- until Ish Watson grabbed the rungs of a passing freight train bound for a dying relative on the Texas Gulf Coast. He brought with him the traits bestowed by his rural upbringing faith, conviction and dedication. But now he faced thundering wheels ready to mutilate and knife-wielding hobos restless to kill, a barreling train anxious to derail and railway "bulls" itching to shoot. Only here in life's trenches would he meet up with the dregs of society: the wayward and the runaways, the dope addicts and the prostitutes, the winos and criminals. The locomotive's black smoke drifted back down the line to cove them all like a shroud, but it was more than death they faced-for this train would not stop until it carried them all to their destinies. And their only hope was Ish's perseverance. This provocative novel, by a finalist for the Spur Award of Western Writers of America, may well challenge your perspective on life.